Static load tests on footings supported by rigid inclusions - Briançon, Laurent; Szymkiewicz, Fabien (Frontiers in Built Environment, 2026)
A series of full-scale static loading tests on square footings supported by rigid inclusions was conducted as part of the French research project ASIRI+. The primary objective of these experiments was to evaluate the impact of a load transfer platform (LTP) between the shallow foundation and rigid inclusions on the performance of the footing and enhanced soil. To achieve this, various loading configurations were examined, including vertical loading with and without eccentricity, as well as horizontal loading, across different structural scenarios—shallow foundations on soil, shallow foundations on reinforced soil with or without a load transfer platform, and rigid inclusions. The comprehensive data obtained from these experiments contribute to a deeper understanding of the load transfer mechanisms in reinforced soil, elucidating the function of each component and facilitating the calibration of numerical models.